A Fort of Nine Towers - Omar, Qais Akbar (London Picador, 2013)
"Qais Akbar Omar's young life coincided with one of the most convulsive decades in Afghan history: civil war, the rise of the Taliban, and the arrival of international troops in 2001. A Fort of Nine Towers, named for the place his parents first sought shelter from war, is the story of Qais's family and their remarkable survival. When the fighting came, this group of tenacious and deeply loving people was buffeted from one part of Afghanistan to the next, 'like kittens in the jaws of a lion'. They set up camp on the plains, in the Buddha caves of Bamiyan, and later with Kuchi nomads, before they were finally able to return to Kabul -- where in many senses their trials were just beginning. As he shares this long journey, through terror, loss, heartbreak, and sudden moments of joy, Qais's spirit never ceases to shine. This is an extraordinary book about a beautiful and civilized country ravaged by war, and about the power of stories to embolden, console, and bind a family together, in the face of almost unimaginable odds."--Publisher's description.
Include Map
Keywords: Afghanistan -- Social conditions -- Omar, Qais Akbar